Spectrophotometric Determination of Ceftotaxime Following Azo Dye Formation with Resorcinol - Muthana S. Mashkoor (Journal of Global Pharma Technology, 2016)
A sensitive, selective, rapid, simple and accurate of the spectrοphotometric determination of ceftotaxime in bulk and in dosage forms. This method depend on diazotization of primary amine group of cefotaxime with sodium nitrate and hydrochloric acid followed by coupling with ceftotaxime in aqueous mildly acidic medium to form azo dye a stable orange. Showed obeyed beers law between 0.5- 15 ppm, with molar absorptive 4.4*104L.mole-1.cm-1 at 456nm.Sandells sensitivity 0.008µg.cm-2, limit of detection (LΟD) 0.185ppm and limit of quantification (LΟQ) 0.619 ppm. This method has been successfully applied to determination of ceftotaxime in bulk and in pharmaceutical preparation, tablet with a good recoveries 99.43-100.32 %.Keyword: Cefotaxime, Resorcinol, Diazotization-coupling, Spectrophotometry.